Paricalcitol alleviates intestinal ischemia-reperfusion injury via inhibition of the ATF4-CHOP pathway - Zhang, Jiawei; Liu, Tingting; Xue, Tongqing; Jia, Zhongzhi (Frontiers in Pharmacology, 2025)
IntroductionIntestinal ischemia reperfusion (I/R) injury is a severe condition characterized by inflammation, oxidative stress, and compromised intestinal barrier function, which can lead to death. This study investigated the effects of paricalcitol, a synthetic vitamin D receptor (VDR) agonist, on intestinal I/R injury, focusing on the activating transcription factor 4 (ATF4)-C/EBP homologous protein (CHOP) signaling pathway and the modulation of endoplasmic reticulum stress (ERS).MethodsThis study consists of both in vivo and in vitro experiments. In vivo experiment, a mouse model of intestinal I/R injury was established by clamping the superior mesenteric artery, and followed by 24 or 72 h of reperfusion. 6-week-old male C57BL/6 J mice were randomly assigned to six groups: sham, I/R 24h, I/R 72 h, and their respective paricalcitol-treated counterparts. VDR knockout mice and wild-type mice were assigned to WT, VDR-KO, WT + I/R and VDR-KO + I/R groups. The paricalcitol-treated groups received oral gavage of paricalcitol (0.3 μg/kg) once daily for 5 days before I/R. In vitro, IEC-6 cells were incubated in a microaerophilic system (5% CO2, 1% O2, 94% N2) for 6 h to induce hypoxia. The cells were then transferred to complete medium with or without paricalcitol (200 nM) and cultured under normoxic conditions for 24 h to establish the hypoxia/re-oxygenation (H/R) model and investigate the protective effects of paricalcitol on H/R-induced injury in cells. We further utilized VDR- and ATF4-silenced cells to examine how paricalcitol regulates the expression of VDR, ATF4, and CHOP.ResultsWe demonstrated that protective paricalcitol treatment reduces ERS and apoptosis by activating VDR and inhibiting the ATF4-CHOP pathway, thereby alleviating intestinal I/R injury in vivo and H/R injury in vitro. Furthermore, experiments with VDR knockout mice demonstrated that the absence of VDR exacerbated I/R injury, underscoring the protective role of VDR in intestinal epithelial cells.DiscussionThese findings suggest that the protective effects of paricalcitol may offer a promising therapeutic strategy for managing intestinal I/R injury.